IMPLEMENTATION OF THE AHP METHOD TO DETERMINE PRIORITIES IN PUBLIC COMPLAINT HANDLING - Dewi Yuliansari, Intan; Elfianty, Lena; Ninosari, Devina (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2025)
Abstract: The Ombudsman of the Republic of Indonesia is an institution tasked with supervising the administration of public services and handling community complaint reports related to allegations of maladministration. The purpose of this research is to create a decision support system using the Analytic Hierarchy Process (AHP) method, which facilitates the determination of priority handling of community complaint reports at the Ombudsman of the Republic of Indonesia Bengkulu Representation. This decision support system is built on a web-based platform using PHP programming language with a MySQL database that can be accessed offline by the admin of the Ombudsman. With the existence of this priority recommendation, it is expected that work will become more effective and efficient, as resources can be focused on reports that most need attention. Based on the test data used, which consists of 12 Community Complaint Reports from July 2024, it was found that the priority handling recommendations for community complaint reports were derived from 3 reports with the highest final AHP values. The recommended priority handling reports are registration number 0021/LM/VII/2024/BKL with a final AHP value of 2.074, registration number 0020/LM/VII/2024/BKL with a final AHP value of 1.964, and registration number 0018/LM/VII/2024/BKL with a final AHP value of 1.866. Keywords: decision support system; priority recommendation; public complaint report; AHP Method (analytic hierarchy process method)